ANALSIS PERKEMBANGAN USAHA MIKRO ANGGOTA KOPERASI BMT UGT SIDOGIRI CABANG SAMARINDA - Evi Nuryaya; Ali Mushofa; Eko Kurniawanto (University of Widya Gama Mahakam Samarinda, 2019)
This research is intended to determine the business development of BMT cooperative members before and after being given funding from BMT UGT Sidogiri Samarinda. The research method used is qualitative, this research is field research (field research) which aims to improve the background, current situation, and environmental interactions that occur in social units. This research was focused on members of the BMT UGT cooperative Sidogiri Samarinda to see micro-business development before and after the funding. The technique of collecting data was carried out by interviewing members of the BMT UGT Sidogiri Samarinda branch and analyzing the results of this study to improve performance before and after giving advice. From the results of the research that can be obtained the largest according to the sellers of rujak with an average value of Rp.66,600,000 with a percentage of capital increase of 50% and turnover of 77.63% and the percentage increase in profits of 108.33% of fish with an average gain of Rp. 135,000,000 percentage increase in capital 20%, turnover of 17.65% and percentage increase in profits of 14.29%. From this analysis can be denied, Members of the BMT UGT cooperative Sidogiri branch Samarinda in micro-business development That is also the funding provided by BMT UGT Sidogiri Samarinda very helpful working capital, and also keep members of the BMT UGT Sidogiri cooperative from the motives of moneylenders and save you Muslims from the practice of usury that is forbidden.